Comprehensive soil greenhouse gas flux dataset from a temperate old-growth forest: Effects of decade-long nitrogen addition and biological factor manipulationzenodo - Junhui Zhang; Yue Gu (Data in Brief)
This dataset presents greenhouse gas (CO₂, CH₄, N₂O) flux measurements and associated environmental variables from a temperate old-growth forest (approximately 300 years old) under different nitrogen addition regimes (control, short-term 1-year, and long-term 10-year treatments) combined with biological factor manipulations (root exclusion, fungal suppression, and litter removal). Data were collected throughout the 2018 growing season (May to September) at 10-day intervals. The dataset includes measurements of three greenhouse gas fluxes, δ¹³C isotopic composition, soil temperature and moisture, pH, ammonium and nitrate nitrogen, dissolved organic carbon, microbial biomass carbon and nitrogen, and total soil carbon and nitrogen. Gas fluxes were measured using the static chamber-gas chromatography method, while soil parameters were determined using standard methods including chloroform fumigation and KCl extraction techniques. The experimental design employed a systematic factorial approach with comprehensive biological factor manipulations. These data can be utilized to analyze the long-term effects of nitrogen deposition on greenhouse gas emissions from forest soils and their biological regulatory mechanisms, providing support for research on global climate change and terrestrial carbon-nitrogen cycling.